Water Level Control and Monitoring Water Temperature in Open Evaporation Pot - Nasruloh, Nasruloh; Raditya Cahya Baswara, Ahmad (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
The tool in this study can control, measure the water level and water temperature in the open evaporation pan automatically. Water level measurements were carried out using the HC-SR04 sensor and water temperature measurements using the DS18B20 sensor. The method used is the Internet of Things (IoT) in order to send data from a NodeMCU type microcontroller as sensor processing and display data on water height, water temperature and control systems stored in databases and websites. The Internet of Things (IoT) can help transmit data remotely to monitor observations of open evaporation pans. The results of the sensor data can be seen through a 20x4 LCD and a website that displays sensor data and the status of the control system on the water pump and solenoid valve. The HC-SR04 sensor can work when the reading is directly into the water without an object. The results obtained are less accurate because the accuracy value on the HC-SR04 sensor is 3mm, while the measuring instrument from BMKG with an accuracy of 0.05mm requires a tool. From the results of the data in this research tool has an average error of 4mm. On the DS18B20 sensor, the resulting value gets an average difference of 0.8 degrees. The water level control system at specified hours with specified conditions works well. Water level data, water temperature can be displayed on the LCD and can be sent via the website once every 1 hour for 24 hours.Alat pada penelitian ini dapat mengontrol, mengukur ketinggian air dan suhu air pada panci penguapan terbuka secara otomatis. Pengukuran ketinggian air dilakukan menggunakan sensor HC-SR04 dan pengukuran suhu air menggunakan sensor DS18B20. Metode yang digunakan adalah Internet of Things (IoT) agar dapat mengirim data dari mikrokontroler dengan tipe NodeMCU sebagai pemrosesan sensor dan menampilkan data tinggi air, suhu air dan sistem kontrol yang disimpan di database maupun website. Internet of Things (IoT) dapat membantu mengirim data dengan jarak jauh agar dapat memantau pengamatan panci penguapan terbuka. Hasil dari data sensor dapat dilihat melalui LCD 20x4 dan website yang menampilkan data sensor dan status sistem kontrol pada water pump dan solenoid valve. Sensor HC-SR04 dapat bekerja ketika pembacaan langsung ke air tanpa objek. Hasil yang didapatkan kurang akurat karena nilai keakuratan pada sensor HC-SR04 yaitu 3mm sedangkan pada alat ukur dari BMKG dengan keakuratan alat dengan kebutuhan 0,05mm. Dari hasil data pada penelitian alat ini mempunyai rata-rata hasil error 4mm. Pada sensor DS18B20 nilai yang dihasilkan mendapatkan nilai rata-rata selisih 0,8 derajat. Sistem kontrol ketinggian air pada jam yang ditentukan dengan syarat yang ditentukan bekerja dengan baik. Data tinggi air, suhu air dapat ditampilkan di LCD dan dapat dikirim melalui website setiap 1 jam sekali selama 24 jam.Â